Expectational Stability of Resonant Frequency Sunspot Equilibria - George W. Evans; Seppo Honkapohja (Center for Economic Studies and ifo Institute (CESifo), 2001)
We consider the stability under adaptive learning of the complete set of solutions to the model when . In addition to the fundamentals solution, the literature describes both finite-state Markov sunspot solutions, satisfying a resonant frequency condition, and autoregressive solutions depending on an arbitrary martingale difference sequence. We clarify the relationships between these solutions and show that the stability properties of equilibria may depend crucially on the representation used by agents in the learning process. Only the finite-state Markov sunspot solutions can be stable under learning.
Keywords: 330; Indeterminacy; representations of solutions; learnability; expectational stability; endogenous fluctuations